The power of concentration: Antipredator responses to diluted frozen crayfish alarm cues provide insights on ecologically relevant concentrations and updates to methodology - Gabrielle H. Achtymichuk; Kaitlyn M. Fish; Maud C. O. Ferrari (PLoS ONE, 2025)
To optimize fitness when facing predation, animals perform threat-sensitive predator avoidance whereby they match the magnitude of the antipredator response to the severity of the perceived threat. Injury-released chemical alarm cues are a reliable indicator of predation risk in aquatic organisms, triggering overt antipredator responses upon detection by conspecifics. Animals with threat sensitivity typically have graded responses to increasing concentrations of these cues which plateau when a maximal response is reached, however, this is undocumented in crayfish. Furthermore, most research currently uses alarm cue exposures consisting of one crushed crayfish diluted in 100–400 mL of water, while it could be ecologically relevant for them to respond to lower concentrations, especially given that predation events can consist of bites or lacerations which would release less alarm cues. The quantity of cue administered into the tank (exposure concentration) is also highly variable, making experimental comparisons difficult. In our study, we collected crayfish alarm cues by rinsing five cut sites (to mimic laceration wounds) and diluting the cues in 100 mL to 100 L of water. Over two experiments, we determined the antipredator response of crayfish exposed to one of five alarm cue concentrations or a water control. During these trials, 20 mL of the cues were administered into 10 L of water, thereby standardizing the test subject’s exposure to the cues. While we failed to find evidence of graded responses, we discovered that alarm cues elicited overt antipredator behaviour when diluted in up to 10 L of water, but this response was lost when cues were diluted in 100 L. Furthermore, this study is the first to successfully use frozen-thawed alarm cues in crayfish. These findings can help direct future research, providing information on the ecologically relevant range of chemical cues and improving welfare by reducing lab-animal sacrifice.